Predictive value of tissue calprotectin for disease recurrence after ileocecal resection in pediatric Crohn's disease - Zarubova, Kristyna; Fabian, Ondrej; Hradsky, Ondrej; Lerchova, Tereza; Mikus, Filip; Dotlacil, Vojtech; Pos, Lucie; Skaba, Richard; Bronsky, Jiri (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
AIM: Detection of possible predictive factors of endoscopic recurrence after ileocecal resection in Crohn's disease could be very beneficial for the individual adjustment of postoperative therapy. The aim of this study was to verify, whether immunohistochemical detection of calprotectin in resection margins is useful in diagnostics of endoscopic recurrence. METHODS: In this study we included pediatric patients with Crohn's disease who underwent ileocecal resection, regardless of pre-operative or post-operative therapy (n=48). We collected laboratory, clinical, surgical, endoscopic and histopathological data at the time of surgery and at 6 months after surgery. The immunohistochemical staining of calprotectin antigen was performed on all paraffin blocks from the resection margins. RESULTS: Out of 48 patients 52% had endoscopic recurrence in the anastomosis (defined by Rutgeerts score) within 6 months after surgery. The number of cells positive for calprotectin in the proximal resection margin was negatively associated with recurrence (P=0.008), as was the elevated level of total calprotectin (from both resection margins). There was no correlation of calprotectin in distal resection margin and endoscopic recurrence. Fecal calprotectin over 100 ug/g (P=0.0005) and high CRP (P<0.001) at 6 months after ileocecal resection and peritonitis (P=0.048) were associated with endoscopic recurrence. CONCLUSION: Approximately half of the patients developed endoscopic recurrence within 6 months after ileocecal resection. The predictive value of tissue calprotectin is questionable, as it is negatively associated with endoscopic recurrence. There are other potentially useful predictors, such as CRP and fecal calprotectin at 6 months after resection and the presence of peritonitis.
Keywords: leukocytární L1-antigenní komplex; Crohn Disease; Recurrence; Feces; kolonoskopie; biologické markery; Biomarkers; resekční okraje; Child; peritonitida; Crohn's disease; dítě; Crohnova nemoc; Colonoscopy; Leukocyte L1 Antigen Complex; recidiva; Peritonitis; Margins of Excision; recurrence; lidé; prediction; Humans; pediatric; calprotectin; feces